2007
DOI: 10.1158/1535-7163.mct-07-0441
|View full text |Cite
|
Sign up to set email alerts
|

Novel E-ring camptothecin keto analogues (S38809 and S39625) are stable, potent, and selective topoisomerase I inhibitors without being substrates of drug efflux transporters

Abstract: Camptothecin (CPT) analogues are powerful anticancer agents but are chemically unstable due to their A-hydroxylactone six-membered E-ring structure, which is essential for trapping topoisomerase I (Top1)-DNA cleavage complexes. To stabilize the E-ring, CPT keto analogues with a five-membered E-ring lacking the oxygen of the lactone ring (S38809 and S39625) have been synthesized. S39625 has been selected for advanced preclinical development based on its promising activity in tumor models. Here, we show that bot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
41
0
3

Year Published

2008
2008
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(44 citation statements)
references
References 37 publications
0
41
0
3
Order By: Relevance
“…In accord, a recent study on the nature of ABCG2 interaction with camptothecin analogs has revealed a similar dependence on the presence of hydroxyl or amine groups on the outer ring of their common camptothecin structure, possibly facilitating hydrogen bond formation, essential for substrate recognition and efflux via ABCG2; these camptothecin positions seem to be analogous to the present R1, R2, or R3 positions of IAs (Yoshikawa et al, 2004). Several subsequent publications on ABCG2-dependent resistance to novel camptothecin analogs have also obeyed this general hydrogen bond rule (Rajendra et al, 2003;Bates et al, 2004;Takagi et al, 2007). Hence, these cumulative results emphasize the robustness of basic structural features of ABCG2 efflux substrates from diverse groups of polyaromatic cytotoxic agents.…”
Section: Discussionmentioning
confidence: 97%
“…In accord, a recent study on the nature of ABCG2 interaction with camptothecin analogs has revealed a similar dependence on the presence of hydroxyl or amine groups on the outer ring of their common camptothecin structure, possibly facilitating hydrogen bond formation, essential for substrate recognition and efflux via ABCG2; these camptothecin positions seem to be analogous to the present R1, R2, or R3 positions of IAs (Yoshikawa et al, 2004). Several subsequent publications on ABCG2-dependent resistance to novel camptothecin analogs have also obeyed this general hydrogen bond rule (Rajendra et al, 2003;Bates et al, 2004;Takagi et al, 2007). Hence, these cumulative results emphasize the robustness of basic structural features of ABCG2 efflux substrates from diverse groups of polyaromatic cytotoxic agents.…”
Section: Discussionmentioning
confidence: 97%
“…In conclusion, taking into account the difficulty to identify novel topoisomerase I inhibitors (4,37), the peculiar features of ST1968 may have obvious therapeutic implications in view of a possible clinical development. …”
Section: Discussionmentioning
confidence: 99%
“…22 Outra maneira de estabilização do anel E é através da retirada do grupo lactônico, que bloqueia completamente a abertura do anel, assim como nos derivados cetônicos que também mantêm a alta atividade anti-TOP1. O derivado ciclobutano metilenodióxi, S39625 (12) está em fase pré-clínica avançada de desenvolvimento, 19,23,24 com resultados mais potentes que a camptotecina em testes com algumas linhagens de células cancerígenas. Outros derivados da camptotecina (13-15) são mostrados na Tabela 1.…”
Section: Interações Dos Anticancerígenos Com Dna Topoisomerasesunclassified
“…Um exemplo pode ser a emodina, ou 1,3,8-tri-hidróxi-6-metilantraquinona (24), isolada do ruibarbo, Rheum palmatum L. (Polygonaceae), que inibe a caseína quinase-2 (CK2).…”
Section: Outros Agentes Anticancerígenos Derivados De Plantas Em Deseunclassified